PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS MELALUI PENDEKATAN KOMUNIKATIF MAHASISWA PROGRAM STUDI BAHASA INGGRIS UNISBA - Dian Dian Fadhilawati (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
This study aims at seeing process freshmen of English Department students at Balitar Islamic University improve their English speaking proficiency implementing communicative approach as the teaching teachniques. This study implemented classroom action research, and was conducted for one semester in the academic year 2014/2015. Improvements were focused on fluency, accuracy and cohesiveness involving 26 subjects.  Conducted in two cycles that succesviley involved research procedures on planning, acting, observing, and reflection, this study revealed the following findings.  First,  speaking fluency of the learners increases from 65% in the first cycle into 85% in the second cycle.  Second, speaking accuracy improves from 68% in the first cycle into 88% in the second cycle.  Third, cohesiveness of uttarences imoproves from 70% in the first cycle into 86% in the sevond cycle.